PROFESSIONAL TRAINING: PROPOSAL FOR INTERVENTION IN A LARGE COMPANY - Cicero da Silva, Luciano; Mendes Nogueira Tolentino, Cintia; Pantaleão da Silva, Cristiano; Ferrancini Ferreira, Erika; Neres dos Santos, Isabela; Beatriz Ribeiro Campos, Giovana (Revista Gênero e Interdisciplinaridade, 2023)
The work organizations in the 21st century have the great challenge of training their work teams, aiming at the development and sustainability of the business. This paper presents an intervention proposal aimed at the development of professionals through the training of technical skills for a better performance of their activities. The organization under study is a medium-sized foundry industry. Based on an information survey and bibliographic research, the need to establish strategies to train professionals was identified, aiming at a better operational performance with a positive impact on the organization’s strategy. The solution proposed for the challenge of developing manpower in a foundry industry consists in the development of partnerships with vocational schools so that in a structured way the professionals can keep themselves constantly trained.